Correlation of Interfacial Transportation Properties of CdS/CdTe Heterojunction and Performance of CdTe Polycrystalline Thin-Film Solar Cells - Guanggen Zeng; Jingquan Zhang; Wenwu Wang; Lianghuan Feng (International Journal of Photoenergy)
The light and dark output performances of CdS/CdTe solar cells made by close-spaced sublimation (CSS) were investigated to elucidate the transportation properties of carriers at CdS/CdTe heterojunction interface. It has been found that the interfacial transportation properties were relatively sensitive to variations of the characteristics of heterojunction due to the series resistance and shunting effects. For the high quality cell with 12.1% efficiency, narrow depletion region of ~1.1 microns and large electric field intensity of ~1.3 V/μm allow the sufficient energy-band bending close to CdS layer at CdS/CdTe heterojunction, which changes the carrier transportation mechanism from emission to diffusion and leads to the optimal rectifying characteristics with small dark saturation current density ~6.4 × 10−10 A/cm2. As a result, the schematic diagram of heterojunction band structure corresponding to various performances of solar cells has also been presented.